Sport Participation and Specialization Characteristics in a Pediatric Sports Medicine Clinic. Issue 5 (31st May 2022) - Worrall, Hannah M.; Cooper, Savannah; Jones, Jacob C.; Miller, Shane M.; Chung, Jane S.
Background: Recent trends in youth sports demonstrate athletes specializing in a single sport at younger ages in an effort to increase athletic success. Research suggests that increased training volume and early sport specialization are associated with increased injury risk, overuse injury, and athlete burnout. Although the exact threshold to avoid injuries has not been elucidated, some pediatric studies have shown increased risk of overuse injury with training more hours per week than their age in years. Hypothesis/Purpose: To determine if athletes presenting to a pediatric sports medicine clinic are participating in more hours per week than their age in years and associated factors related to sport participation. Methods: Data were prospectively collected from participants who presented to a tertiary sports medicine clinic for injury evaluation between October 2016-May 2021. Participants aged 5-<19 years who reported playing sports and had hours per week in their primary sport documented were included. Demographic and sport-related variables were reviewed. Participants were separated into two groups based on whether number of hours per week in their primary sport exceeded their age: UNDER (chronologic age and under) and OVER. Results: 10, 586 total participants: 8846 (83.6%) UNDER and 1740 (16.4%) OVER. There was no difference in age (13.7±2.6 vs 13.6±2.6 years, p=0.27) between the UNDER and OVER group. There were more males (49.7 vs 38.5%, p<0.0001) and more Hispanic or Latinos (20.2 vs 16.4%, p<0.0001) in the UNDER compared to the OVER group. Soccer (23.0%) was the most common primary sport for the UNDER group while gymnastics (27.1%) was for the OVER group. More participants considered themselves single-sport athletes (68.5 vs 54.1%, p<0.0001) and reported their highest level of competition as club/select/travel (52.0 vs 38.2%, p<0.0001) in the OVER group than the UNDER group. The OVER group reported a significantly higher number of sport participation hours per week than the UNDER group (20.5±8.2 vs 6.9±3.7 hours, p<0.0001, Figure 1), an additional year (6.8±3.2 vs 5.6±3.3 years, p<0.0001), and weeks per year participating in their primary sport (41.7±13.4 vs 32.0±15.5 weeks, p<0.0001). Conclusion: About 15% of athletes seen at the sports medicine clinic reported participating in more hours per week than their age. These athletes were more likely to report being single-sport athletes and participating in club-style teams. Understanding this information may aid providers in educating families in the OVER group about potential increased risk for injury due to high weekly participation volumes and sport specialization. Figure 1. Average number of participation hours per week in the OVER compared to the UNDER group